Redescription of Malacosarcus macrostoma (Günther, 1878) from the abyssal zone off Taiwan, northwestern Pacific Ocean (Beryciformes, Stephanoberycoidei, Stephanoberycidae) - Yo Su; Mao-Ying Lee; Hsuan-Ching Ho (ZooKeys)
The large-mouth pricklefish, Malacosarcus macrostoma (Günther, 1878), previously known from five specimens collected from the central Pacific Ocean, is redescribed based on three specimens collected from the abyssal zone (4,412–4,813 m) off the southeastern coast of Taiwan. These specimens contribute to a more comprehensive description of M. macrostoma and represent this species’ westernmost and deepest record. This study provides a detailed description, fresh photographs, and notes on their morphological characteristics of the specimens. Lastly, the distributional records of M. macrostoma are discussed.